Dopamine Pathway Mediated by DRD5 Facilitates Tumor Growth via Enhancing Warburg Effect in Esophageal Cancer - Qian, Xiaozhe; Zhang, Donglei; Cao, Ziang; Ma, Haitao (Frontiers in Oncology, 2021)
Esophageal cancer (EC) is among the most malignant cancers globally due to its aggressiveness and poor survival. To set off from the inflammatory tumor immune microenvironment, we analyzed tumor tissues of EC patients with or without lymphatic metastasis to explore the importance of cancer cell derived neurotransmitters. Results have emphasized that the accumulation of dopamine but not other neurotransmitters could be observed in EC tumor tissue of patients, especially who bearing lymphatic metastasis. Transcriptional analysis of mentioned tissues was also performed to filter out key enzymes involved in dopamine pathway including tyrosine hydroxylase (TH), DOPA decarboxylase (DCC) and monoamine oxidase (MAO), etc. Further analysis on tumor tissues of patients indicated that dopamine receptor D5 was aberrantly upregulated and co-located with TH. Both in vitro and in vivo tests have demonstrated that dopamine could stimulate the proliferation and outgrowth of EC tumor cells via DRD5 mediated pathway. The exploration of mechanism has unveiled that activation of dopamine pathway significantly enhanced the uptake of glucose and production of lactate of EC tumor cells. It can also facilitate the extracellular acid rate (ECAR), dedicating that DRD5-mediated activated dopamine pathway could effectively form and trigger Warburg Effect, which is modulated by the cross-talk of mTOR and AKT pathway. Our results would unveil the relationship between cancer derived neurotransmitters and inflammatory tumor immune microenvironment, thus provide potential therapeutic targets and novel clinical strategy towards metastatic EC.